Blockchain and Climate Action : Enhancing ESG and Carbon Markets Through Financial Technology - Dominik Skauradszun; Walter Blocher; Florian Möslein; Carsten Müller; Eric Nowak; Nils Urbach; Georg von Wangenheim (De Gruyter, 2025)
The book provides an analysis of the challenges associated with the utilisation of blockchain technology in carbon markets and ESG from various academic disciplines. The analysis of the tokenisation of Voluntary Carbon Credits (VCC) using blockchain technology will encompass a comprehensive review of the issues involved in the economics of Voluntary Carbon Markets (VCM), the development of business models, the technology employed, and the legal aspects from civil and regulatory law.